Venous drainage of fore-foot of camel (Camelus dromedarius) - JAIN, R K; DHINGRA, L D (The Indian Journal of Animal Sciences, 2013)
The venous drainage of the fore-foot of camel was curried out by a dorsal venous system and a palmar venous system, The origin, course and termination of these veins have been described through venography and gross dissections.